MANAJEMEN ASET BERGERAK KENDERAAN BERMOTOR PADA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN GORONTALO - Lamangida, Trisusanti; Harun, Nahrois (JSAP : Journal Syariah and Accounting Public, 2021)
This study aims to determine the movable asset management of motorized vehicles at the Population Control and Family Planning Office of Gorontalo Regency. The results of the study concluded that the management of motorized vehicle movable assets at the Gorontalo District Population Control and Family Planning Office was generally not optimal. In particular, the aspects of use, utilization, safeguarding and maintenance of assets have not been going well and are still far from expectations. Planning for asset requirements and procurement of appraisal, deletion, transfer, administration, and guidance, supervision and control at the Gorontalo District Population and Family Planning Office has been running but has not been maximized. It is recommended that local governments evaluate and improve the management of regional assets in Gorontalo District, especially in terms of use, utilization, security and maintenance of assets.